Apologetic Communication - Hübenthal, Christoph (International journal of public theology, 2016)
Though apologetics is a contested concept in current theological debates, leading representatives of public theology still see apologetics as the core of their theological endeavours. This article develops a concept of apologetic communication that emerges from a particular understanding of theology. Theology, as will be argued, serves the Christian faith praxis as well as the validity claims underlying this praxis. A closer analysis of these validity claims will reveal that their public verification requires two discriminable but interrelated types of communication, namely discourse and witnessing. Consequently, a discursive and testimonial type of apologetic communication will be distinguished. In the last section some suggestions will be made on how public theology should operate if it takes its apologetic task seriously. The central thesis will be that apologetic communication in both its modes appears as a form of ethics: as ethical reflection and ethical behaviour.